High Production of 2,3-Butanediol (2,3-BD) by Raoultella ornithinolytica B6 via Optimizing Fermentation Conditions and Overexpressing 2,3-BD Synthesis Genes - Kim, Taeyeon; Cho, Sukhyeong; Lee, Sun-Mi; Woo, Han Min; Lee, Jinwon; Um, Youngsoon; Seo, Jin-Ho (Public Library of Science, 2016)
Biological production of 2,3-butandiol (2,3-BD) has received great attention as an alternative to the petroleum-based 2,3-BD production. In this study, a high production of 2,3-BD in fed-batch fermentation was investigated with a newly isolated bacterium designated as Raoultella ornithinolytica B6. The isolate produced 2,3-BD as the main product using hexoses (glucose, galactose, and fructose), pentose (xylose) and disaccharide (sucrose). The effects of temperature, pH-control schemes, and agitation speeds on 2,3-BD production were explored to optimize the fermentation conditions. Notably, cell growth and 2,3-BD production by R. ornithinolytica B6 were higher at 25 degrees C than at 30 degrees C. When three pH control schemes (no pH control, pH control at 7, and pH control at 5.5 after the pH was decreased to 5.5 during fermentation) were tested, the best 2,3-BD titer and productivity along with reduced by-product formation were achieved with pH control at 5.5. Among different agitation speeds (300, 400, and 500 rpm), the optimum agitation speed was 400 rpm with 2,3-BD titer of 68.27 g/L, but acetic acid was accumulated up to 23.32 g/L. Further enhancement of the 2,3-BD titer (112.19 g/L), yield (0.38 g/g), and productivity (1.35 g/L/h) as well as a significant reduction of acetic acid accumulation (9.71 g/L) was achieved by the overexpression of homologous budABC genes, the 2,3-BD-synthesis genes involved in the conversion of pyruvate to 2,3-BD. This is the first report presenting a high 2,3-BD production by R. ornithinolytica which has attracted little attention with respect to 2,3-BD production, extending the microbial spectrum of 2,3-BD producers.